Solar Cells Produced by Diamond Wire Sawn Multicrystalline Silicon Wafer by Using Additive-Assisted Acidic Texturization - Jie Sun; Yan Zuo; Runguang Sun; Lang Zhou (Advances in Materials Science and Engineering)
A novel additive-assisted acidic etching method is proposed to improve the etched morphology of the diamond wire sawn (DWS)-processed multicrystalline silicon (mc-Si) wafers. The proposed etching technique is a cost-effective method for surface texturization of DWS-processed mc-Si wafers, which can be used for large-scale production of Si-based solar cells. Moreover, the mechanism of additive-assisted etching is explained by decoupling the roles of surfactants and etching inhibitors. The additive-assisted etching of DWS-processed mc-Si wafers resulted in different morphology to the slurry wire sawn (SWS)-processed mc-Si wafers under optimized etching conditions. It has been observed that the etched morphology and reflectivity of DWS-processed mc-Si wafers are significantly influenced by the ratio of hydrofluoric acid (HF): nitric acid (HNO3) solution. High-quality etching morphologies have been obtained. Therefore, high-power conversion efficiency of 19.0% and open-circuit voltage (Voc) of 0.6386 V have been demonstrated by additive-textured DWS-processed Si-based solar cells. The improved power conversion efficiency and Voc can be ascribed to the reduced defect area of the wafer surface. In summary, the proposed additive-assisted acidic etching is an effective strategy to obtain the desired surface texturization of DWS-processed Si wafers for high-performance solar cell applications.